America's Israel : the U.S. Congress and American-Israeli relations, 1967-1975 - Kolander, Kenneth, 1981- (Studies in conflict, diplomacy, and peace, 2020)
"One of the defining features of US foreign relations for the past 50 years has been the nation's relationship with Israel. This informal alliance, rooted in shared values and culture, grew out of a moral obligation to help preserve Israel's survival in the aftermath of the Holocaust as US policymakers provided military aid, weapons, and political protection. In return, Israel served US interests through efforts to contain communism in the region. Between 1967 and 1975, the United States centered itself as peacemaker in the Middle East and became Israel's biggest supporter, spurring their special relationship beyond just a moral commitment. By the end of 1975, the US pledged to provide for the economic and military needs of Israel, while also supporting the retention of territories obtained during the Six-Day and Yom Kippur Wars. Such decisions cemented the bond between the two nations. Today, the US provides almost four-billion dollars in military aid per year, which raises questions regarding interest and propriety: At what point does US military aid and political protection for Israel exceed the boundaries of their unconventional relationship? Is any amount of military aid an expression of the special relationship? When does US support for Israel become counter-productive to other US interests, as well as the pursuit of peace in the Middle East? In America's Israel: The US Congress and American-Israeli Relations, 1967-1975, author Kenneth Kolander explores the answers to these questions. In addressing the role of Congress in the creation of the US-Israel bond, he gives deeper consideration to national security concerns, cultural similarities, and the importance of domestic politics. Kolander argues that the imbalance in scholarly perspective about US-Israel relations has created a misleading narrative, treating the legislative branch as supplementary to foreign policymaking. By correcting this imbalance, Kolander seeks to connect popular affinity for Israel with the development of the US government's pro-Israel stance"--